2017
DOI: 10.1007/s00113-016-0291-0
|View full text |Cite
|
Sign up to set email alerts
|

Tendinopathien bei rheumatischen Erkrankungen

Abstract: Involvement of tendons and tendon sheaths is frequently found in the most common inflammatory systemic diseases, rheumatoid arthritis and spondyloarthritis. In rheumatoid arthritis tendon manifestations occur as tenosynovitis, with swelling and pain of the tendons mainly on the hands and feet. In spondyloarthritis the involvement of tendons presents as enthesitis with pain and swelling directly at the attachment points of tendons to the bony structures and more commonly in the lower extremities. Pathological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
3
0
3
Order By: Relevance
“…Nahezu alle operativen Eingriffe an der rheumatischen Hand bedürfen einer konsequenten, oft langwierigen und mühseligen krankengymnastischen und ergotherapeutischen Nachbehandlung 3 . In vielen Fällen ist auch eine präoperative Behandlung unter Anwendung dynamischer Handorthesen, die nach der Operation weiterverwendet werden, erforderlich 14 Die krankengymnastische Nachbehandlung muss möglichst früh nach der Operation (manchmal noch am Operationstag) einsetzen. Sie muss unter Vermeidung von Schmerzen und unterstützt durch lokale Kryotherapie allmählich gesteigert werden, wobei aktiven Bewegungen der Vorrang vor passiven zu geben ist.…”
Section: Vor- Und Nachbehandlungunclassified
See 1 more Smart Citation
“…Nahezu alle operativen Eingriffe an der rheumatischen Hand bedürfen einer konsequenten, oft langwierigen und mühseligen krankengymnastischen und ergotherapeutischen Nachbehandlung 3 . In vielen Fällen ist auch eine präoperative Behandlung unter Anwendung dynamischer Handorthesen, die nach der Operation weiterverwendet werden, erforderlich 14 Die krankengymnastische Nachbehandlung muss möglichst früh nach der Operation (manchmal noch am Operationstag) einsetzen. Sie muss unter Vermeidung von Schmerzen und unterstützt durch lokale Kryotherapie allmählich gesteigert werden, wobei aktiven Bewegungen der Vorrang vor passiven zu geben ist.…”
Section: Vor- Und Nachbehandlungunclassified
“…Die Arthrodese ist an den Endgelenken und insbesondere am Daumengrundgelenk ein dankbarer Eingriff 14 , zur Verbesserung der Griffkraft und zur Reduzierung der Schmerzen verbunden mit wiederkehrender Stabilität.…”
Section: Diskussionunclassified
“…As suggested by Maffulli et al [2], the term tendinopathy can be used as a general descriptor of the clinical conditions arising from tendon overuse, independently from histopathological damage. The term "tendinopathy" should include different pathologies such as tendinitis, tendinosis, and para-tendinitis (which includes peritendinitis, tenosynovitis and tenovaginitis) [2,3]. Focusing on different changes that may occur in tendon structure in tendinopathies, it could be distinct: tendinitis, inflammation and pathological changes of tendons; tendinosis, non-inflammatory tendon degeneration; peri-tendinitis, inflammation due to friction against a surface during tendon movement; tenosynovitis and tenovaginitis, single or double-layer inflammation of tendon sheath [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The term "tendinopathy" should include different pathologies such as tendinitis, tendinosis, and para-tendinitis (which includes peritendinitis, tenosynovitis and tenovaginitis) [2,3]. Focusing on different changes that may occur in tendon structure in tendinopathies, it could be distinct: tendinitis, inflammation and pathological changes of tendons; tendinosis, non-inflammatory tendon degeneration; peri-tendinitis, inflammation due to friction against a surface during tendon movement; tenosynovitis and tenovaginitis, single or double-layer inflammation of tendon sheath [2,3]. Therefore, considering all these different definitions, Maffulli et al [2] suggested to use the term "tendinopathy" as a general descriptor of all these clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with rheumatoid arthritis or other inflammatory systemic diseases, it is impossible to separate an idiopathic trigger finger from a triggering due to a rheumatoid manifestation 119 . A rheumatic trigger finger usually presents as tenosynovitis, and is associated with swelling and pain.…”
Section: Trigger Finger In Rheumatoid Arthritismentioning
confidence: 99%